S80 Localisation of the site of fixed airflow obstruction in moderate to severe asthma using hyperpolarised helium-3 MRI. (2nd December 2011) - Gonem, S; Ball, I; Corkill, S; Desai, D; Singapuri, A; Gustafsson, P; Owers-Bradley, J; Brightling, C; Siddiqui, S
Abstract : Introduction and Objectives: Moderate and severe asthma are often associated with a degree of fixed airflow obstruction. We aimed to comprehensively characterise a group of patients with moderate to severe asthma using a variety of standard and novel physiological techniques, including hyperpolarised helium-3 magnetic resonance imaging (He-3 MRI), in order to non-invasively localise the major site of airway obstruction within the bronchial tree. Methods: We recruited 17 patients with moderate asthma (GINA 3/4), 12 patients with severe asthma (GINA 5) and fifteen healthy control subjects. Participants undertook standard pulmonary function tests, multiple breath washout (MBW) and impulse oscillometry (IOS). Five healthy subjects and 10 patients with asthma also undertook He-3 MRI. Two MRI sequences were performed. The first sequence allowed derivation of the apparent diffusion coefficient (ADC), a measure of alveolar airspace size, while the second sequence allowed derivation of the modelled parameters R and h, representing acinar outer airway radius and alveolar sleeve width respectively, as introduced by Yablonskiy et al .1 Results: Patients with asthma displayed evidence of fixed airflow obstruction and air trapping, with reduced FEV1 and increased RV/TLC ratio, compared to healthy controls. However, Kco was higher in patients with asthma than in controls. The MBW small airway marker Sacin was significantly raised in patients with asthma compared to healthy controls (healthy=0.126, GINA 3/4 asthma=0.173, GINA 5 asthma=0.213; p=0.03), confirming the presence of acinar airspace disease in patients with moderate and severe asthma. Scond, a conductive airway marker, did not differ significantly between the groups. ADC, R and h also did not differ significantly between healthy controls and patients with asthma, or between asthmatic patients with and without evidence of acinar airspace disease ( see Abstract S80 figure 1 ), suggesting that the alveoli are not a major site of involvement in asthma. Conclusion: Our results suggest that the site of fixed airflow obstruction in patients with moderate to severe asthma may be localised to the proximal acinus, and that the alveoli are relatively spared.